EBV Infection Alters NK Cell Phenotype Distinctly From hCMV - Ustiuzhanina, Maria O; Vavilova, Julia D; Salnikova, Maria A; Chertkova, Aglaya A; Alekseeva, Nadezhda A; Boyko, Anna A; Palamarchuk, Anastasia I; Streltsova, Maria A; Chudakov, Dmitriy M; Kovalenko, Elena I (Journal of medical virology, 2025)
Natural killer (NK) cells are vital in the antiviral response regulated by inhibitory and activating receptors, including NKG2 and KIR families, which bind HLA-I. While the adaptive features of NK cells in response to human cytomegalovirus (hCMV) have been well described, their behavior during Epstein-Barr virus (EBV) infection and the influence of KIR-HLA combinations in healthy carriers of these viruses remains unclear. We performed high-resolution HLA genotyping, phenotypic profiling of NK cell subsets, and serological testing for hCMV and EBV-specific IgG in 85 healthy adult donors. hCMV-seropositive individuals exhibited significant expansions of NKG2C+ and HLA-DR+ NK cell subsets, with the proportion of NKG2C+ cells strongly correlating with hCMV-IgG titers. In contrast, EBV infection was associated with increased frequencies of terminally differentiated CD56dim, NKG2A-, CD57+ NK cells and elevated expression of inhibitory KIRs, but not NKG2C or HLA-DR. EBV-IgG titers correlated with CD57 and KIR2DS4 levels. Among KIR2DS4-expressing donors, carriage of at least one HLA-C2 allele was associated with elevated EBV-IgGs. The precise analysis of KIR2DL2/DL3, KIR2DS4, and KIR2DL1 revealed dependencies on EBV-IgG titers, with no associations with hCMV. These findings highlight the differential impacts of hCMV and EBV on NK cells and underscore the relevance of HLA-KIR landscapes in shaping antiviral immunity.
Keywords: Young Adult; Immunoglobulin G; fenotyp; Male; Phenotype; Cytomegalovirus Infections; HLA; protilátky virové; Middle Aged; Epstein-Barr Virus Infections; hCMV; Genotype; mladý dospělý; antiviral immunity; Herpesvirus 4, Human; virus Epsteinův-Barrové; Adult; infekce virem Epsteina-Barrové; NK Cell Lectin-Like Receptor Subfamily C; imunoglobulin G; dospělí; mužské pohlaví; NKG2; HLA antigeny; cytomegalovirové infekce; Receptors, KIR; lidé; ženské pohlaví; Humans; buňky NK; EBV; HLA Antigens; NK cells; Cytomegalovirus; genotyp; Antibodies, Viral; KIR; Killer Cells, Natural; Female; receptory KIR; lidé středního věku; lektinové receptory NK-buněk - podrodina C